Effect of refrigeration and frozen storage on the Campylobacter jejuni recovery from naturally contaminated broiler carcasses - Maziero,Maike T. (2010)
Campylobacter jejuni is the most common thermophilic Campylobacter associated with human enteritis in many countries. Broilers and their by-products are the main sources for human enteritis. Refrigeration and freezing are used to control bacterial growth in foods. The effect of these interventions on survival of Campylobacter jejuni is yet not quite understood. This study evaluated the effect of storage temperature on the survival of C. jejuni in chicken meat stored for seven days at 4ºC and for 28 days at -20ºC. The influence of selective enrichment on recovery of Campylobacter was also evaluated. Thirty fresh chicken meat samples were analyzed and 93.3% was contaminated with termotolerant Campylobacter spp. with average count of 3.08 Log10 CFU/g on direct plating. After refrigeration, 53.3% of the analyzed samples tested positive for Campylobacter and the average count was 1.19 Log10 CFU/g. After storage at -20ºC, 36.6% of the samples were positive with a verage count of 0.75 Log10 CFU/g. C. jejuni was detected after enrichment, respectively, in 50% of the fresh, 36.7% of the refrigerated and 33.3% of the frozen meat samples analyzed. No difference was detected for the recovery of C. jejuni from fresh, refrigerated or frozen samples after selective enrichment, showing that this microorganism can survive under the tested storage conditions.